Hygiene of healthcare organizations: tutorial : for medical studentsГигиена лечебно-профилактических организаций: учебно-методическое пособие - Кавешников, В. С. кардиология 19750627 Владимир Сергеевич (Сибирский государственный медицинский университет, 2018)
The tutorial is prepared in accordance with the Federal State Educational Standard of Higher Professional Education, for medical students. The textbook is based on the publication in Russian "Guide to Practical Training on Hygiene". The tutorial has been revised and supplemented. Present hygienic problems of hospital buildings, hygienic requirements for location, planning and equipment of hospitals are described in the tutorial.